Saudi Arabia's national interests in military intervention policy in Yemen against Iranian involvement - Bahein, Najm Al-Dain S.M. (ARKA INSTITUTE, 2025)
The Yemeni Civil War, which has been ongoing since 2015, has attracted significant international attention due to its complex dynamics and severe humanitarian consequences. Among the main actors involved, Saudi Arabia’s intervention played a crucial role in shaping the trajectory of the conflict. This study analyzes Saudi Arabia’s intervention’s motivation, nature, and impact, especially in its geopolitical rivalry with Iran and broader national interests. This study uses a qualitative approach. Data was collected through various scholarly sources and empirical data. The study evaluates the military, political, and humanitarian dimensions of Saudi Arabia’s involvement as well as its regional and global implications. The findings of this study reveal that Saudi Arabia’s intervention was primarily driven by security concerns, economic interests, and the pursuit of regional dominance rather than solely in response to Iranian influence. However, the protracted nature of the conflict and its humanitarian consequences highlight the challenges Saudi Arabia faces in achieving its objectives. By contextualizing these results within a broader socio-political framework, this study provides a deeper understanding of the Yemeni crisis and the role of external actors, particularly Saudi Arabia, in shaping its development.